Systematic Literature Review: Optimizing the Use of Case Based Learning Models in Augmented Reality Media to Enhance Student Engagement and Critical Thinking - Marcel Prastiko Arthana; Ketut Agustini; I Kadek Suartama (Thinking Skills and Creativity Journal, 2025)
The integration of the Case Based Learning (CBL) model with Augmented Reality (AR) has gained increasing attention as an innovative educational approach; however, its effectiveness in enhancing student engagement and critical thinking remains underexplored. This study aims to analyze the implementation of the combined CBLAR model and evaluate its impact on active engagement and critical thinking across various formal education levels. A systematic literature review using the PRISMA framework was conducted, analyzing 21 relevant journals selected from an initial 150 sources obtained through the Publish or Perish application and Google Scholar. The study examined diverse learning contexts implementing CBL AR integration. Data were analyzed thematically to identify trends, model effectiveness, integration strategies, and their effects on student engagement and critical thinking. Findings indicate that CBL AR integration significantly enhances students’ active participation, promotes critical thinking skills, and strengthens conceptual understanding through immersive and contextual learning experiences. The combination of CBL’s reflective and problem solving structures with AR’s narrative and interactive visualizations supports the development of 21st century skills. The study concludes that the effectiveness of the CBL AR model strongly depends on digital infrastructure readiness and educators’ competencies. Practically, professional development for teachers and institutional investment in technology are strategic priorities to maximize the adoption and effectiveness of this model widely.